Anti-aging Effect of Allium pseudojaponicum in UVA–irradiated Human Epidermal Keratinocytes: Anti-aging Effect of Allium pseudojaponicum - Shim, Joong Hyun (Cellular and Molecular Biology, 2023)
This study was conducted to investigate the anti-aging effects of Allium pseudojaponicum extract on normal human epidermal keratinocytes (NHEKs). The effects were examined by analyzing gene expressions related to skin hydration using quantitative real-time polymerase chain reaction (qRT-PCR), hyaluronic acid (HA) production using HA-ELISA, cell viability using a cell viability assay, and a phospho-kinase array. Allium pseudojaponicum extract increased the gene expression levels of AQP3/HAS2 and HA protein production in NHEKs while decreasing the overexpressed mRNA levels of KRT1, 10 and FLG genes, known as differentiated keratinocyte markers in NHEKs. Additionally, A. pseudojaponicum extract reduced the phosphorylation of CHK2 and p53 proteins, which are related to cell cycle or epidermal differentiation. This study demonstrated the anti-aging effects of A. pseudojaponicum extract, which could potentially be used as a functional ingredient for skin hydration and anti-aging products.